2019
DOI: 10.1021/acs.macromol.9b00857
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Alkyl Diazoacetates Initiated by Pd(Naphthoquinone)/Borate Systems: Dual Role of Naphthoquinones as Oxidant and Anionic Ligand for Generating Active Pd(II) Species

Abstract: For polymerization of alkyl diazoacetates, the combination of a Pd complex bearing 1,4-naphthoquinone (NQ) or its derivatives as a ligand and borate, NaBPh4, was found to be an efficient initiating system. The polymerization of ethyl diazoacetate by a Pd(0) complex having two NQ molecules [Pd­(nq)2] with NaBPh4 proceeded to give poly­(ethoxycarbonylmethylene)­s with a relatively high molecular weight (up to M n = 36 kDa) in good yield (∼70%). This initiating system was also effective for polymerizing other dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 58 publications
4
26
0
Order By: Relevance
“…The GC−MS analysis of the IMesPd(cinn)Cl−NaBARF reaction mixture (1:1) showed the presence of organic products containing a 3,5bis(triflluoromethyl)phenyl moiety after storing the mixture for a day. Thus, in addition to the abstraction of Cl − from the initial (NHC)Pd complexes, NaBARF can be involved in a reaction with Pd complexes, resulting in the cleavage of B−Ar F bonds and the formation of Pd−Ar F species (the cleavage of B−Ar bonds by Pd compounds is well-documented 66,67 ). In this case, the decomposition of the BARF − anion occurs; therefore, it is desirable to use an excess of NaBARF as a cocatalyst for addition polymerization in the presence of The most effective cocatalysts are NaBARF and LiFABA, while the catalyst systems with DANFABA or AgBF 4 as a cocatalyst are less active.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The GC−MS analysis of the IMesPd(cinn)Cl−NaBARF reaction mixture (1:1) showed the presence of organic products containing a 3,5bis(triflluoromethyl)phenyl moiety after storing the mixture for a day. Thus, in addition to the abstraction of Cl − from the initial (NHC)Pd complexes, NaBARF can be involved in a reaction with Pd complexes, resulting in the cleavage of B−Ar F bonds and the formation of Pd−Ar F species (the cleavage of B−Ar bonds by Pd compounds is well-documented 66,67 ). In this case, the decomposition of the BARF − anion occurs; therefore, it is desirable to use an excess of NaBARF as a cocatalyst for addition polymerization in the presence of The most effective cocatalysts are NaBARF and LiFABA, while the catalyst systems with DANFABA or AgBF 4 as a cocatalyst are less active.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…NMR analyses of the polymers revealed that 1−3/NaBPh 4 produced atactic polymers, as is the case with the previously reported Pd(nq) 2 /NaBPh 4 initiating system. 36 Representative 1 H and 13 C NMR spectra of the polymers obtained by 1−3/ NaBPh 4 are shown in the Supporting Information.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…32−37 Among the latter, the (π-allylPdCl) 2 /NaBPh 4 system 34,37 has been demonstrated to produce atactic PACMs with various functional groups with moderate to high molar mass in good yield. Noteworthy, the initiating system can polymerize diazoacetates having bulky ester substituents in a controlled manner to give PACMs with relatively narrow molar-mass distribution; 11 thus, utilizing the controlled polymerization, we have successfully synthesized well-defined block copolymers composed of soft and hard PACM blocks Besides the above-mentioned divalent π-allylPd-based initiating systems, we recently found that a zerovalent Pd complex, Pd(nq) 2 (nq = 1,4-naphthoquinone), was quite effective for the polymerization of diazoacetates in terms of molar mass and yield of obtained polymers; 36 the combination of Pd(nq) 2 and NaBPh 4 polymerized various diazoacetates to give PACMs with higher molar mass and yield compared with the π-allylPdCl/NaBPh 4 initiating system. In the Pd(nq) 2 / NaBPh 4 initiating system, the initiating Pd species is supposed to be a Pd(II) complex with an η 3 -naphthoquinonyl ligand, which should be generated via "oxidative transmetalation", where transmetalation of a Ph group from NaBPh 4 to Pd occurs simultaneously with oxidation of the Pd center resulting in the formation of a Pd(II)−Ph complex with an η 3naphthoquinonyl ligand, on the basis of a study reporting a related transformation (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Remarkably, the Rh-mediated polymerization of ethyl and benzyl diazoacetates reported by de Bruin and co-workers afforded polymers with high molecular weights and high stereoregularity. On the other hand, extensive work by Ihara and co-workers identified a series of (π-allyl)­PdCl-based systems that could initiate the polymerization of various diazoacetates (Scheme ). Furthermore, they also carried out detailed studies on (π-allyl)­PdCl-based systems and other palladium initiators. Recently, Wu and co-workers reported a living/controlled polymerization of various diazoacetates using (π-allyl)­PdCl ligated with bulky chiral bidentate phosphine ligands bearing a sulfinamide moiety. , Toste and co-workers studied the polymerization of diazoacetate with (π-allyl)palladium carboxylate dimers, demonstrating that the polymerization with such initiators occurred in a controlled quasi-living manner . While extensive studies have been devoted to C1 polymerization with diazoacetates, it is still highly desirable to search for new polymerization catalysts that can efficiently initialize the polymerization with diazoacetates in a controlled manner.…”
Section: Introductionmentioning
confidence: 99%